Safety of COVID-19 Pfizer-BioNtech (BNT162b2) mRNA vaccination in adolescents aged 12-17 years: A systematic review and meta-analysis - Patrick D. M. C. Katoto; Amanda S. Brand; Liliane N. Byamungu; Jacques L. Tamuzi; Tamirirashe C. Mahwire; Marcel K. Kitenge; Charles S. Wiysonge; Glenda Gray (Taylor & Francis Group, 2022)
The COVID-19 pandemic has severely affected adolescents. Safe and effective vaccines are pivotal tools in controlling this pandemic. We reviewed the safety profile of the BNT162b2 COVID-19 vaccine in adolescents using mostly real-world data to assist decision-making. We used random-effects model meta-analysis to derive pooled rates of single or grouped adverse events following immunization (AEFI) after each primary and booster dose, as well as after combining all doses. Reporting on over one million participants with safety data were included. The most-reported local and systemic AEFIs were pain/swelling/erythema/redness and fatigue/headache/myalgia, respectively. AESIs were rarely reported but were more frequent after the second dose than they were after the first and the booster doses. Health impact was less common among adolescents after receiving BNT162b2 vaccine. Rare life-threatening AEFIs were reported across all doses in real-world studies. Our findings highlight the significance of enhancing national and regional vaccination programs to ensure public confidence.